2011
DOI: 10.1002/ajmg.a.34260
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of intercentromeric distance, mosaicism, and sexual phenotype: Molecular localization of breakpoints in isodicentric Y chromosomes

Abstract: Isodicentric chromosomes are among the structural abnormalities of the Y chromosome that are commonly identified in patients. The simultaneous 45,X cell line that is generated in cell division due to instability of the isodicentric Y chromosome [idic(Y)] has long been hypothesized to explain the variable sexual development of these patients, although gonads have been studied in only a subset of cases. We report here on the molecular localization of breakpoints in ten patients with an idic(Y). Breakpoints were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 20 publications
0
28
0
2
Order By: Relevance
“…Three of our patients (cases 8, 10 and 11) had a breakpoint within regions consisting of palindromes [26,27], which may have contributed to the emergence of these deletions [26,27]. …”
Section: Discussionmentioning
confidence: 99%
“…Three of our patients (cases 8, 10 and 11) had a breakpoint within regions consisting of palindromes [26,27], which may have contributed to the emergence of these deletions [26,27]. …”
Section: Discussionmentioning
confidence: 99%
“…A similar situation is described for buccal cells of ectodermic origin [32]. Relying on the formation of mosaics in patients with rearranged, dicentric Y chromosomes, some authors suggest that a greater instability of the aberrant Y chromosome might promote its loss during the cell divisions of the germline, thus, promoting the development of a female habitus [34].…”
Section: Mosaicsmentioning
confidence: 66%
“…This idic(Y) was present in all 40 metaphases analyzed, indicating stability of the abnormal chromosome. Bergeron et al [2011] suggested that the intercentromeric distance has a negative influence on the stability of idic(Y), since a greater proportion of cells with breakage or loss of the idic(Y) were found in idic(Y) cases with a greater intercentromeric distance. In fact, our patient presents the smallest intercentromeric distance compared to the 10 idic(Y) patients reported by Bergeron et al [2011].…”
Section: Discussionmentioning
confidence: 99%